Advanced concept of drive shaft system for hybrid high speed helicopter - Cander, D.; Geneix, J.; Depouhon, P. (My University, 2019)
In this paper, a new advanced concept of supercritical drive shaft system has been described. It is intended to work inside an aircraft’s wing, in very demanding conditions, such as narrow available space with a simultaneous significant relative displacement between sub-systems, transmitting higher mechanical power than conventional shafts. The standard approach, to design drive shafts, has been reconsidered and adapted to new requirements. This technology has been applied first to the X3 demonstrator and is pushed to a new leading edge level on the Rapid and Cost- Effective Rotorcraft (RACER) demonstrator. It is a hybrid high speed helicopter funded jointly by Airbus Helicopters and European Commission in frame of Clean Sky 2.